Pengabdian Masyarakat Tentang Pentingnya Investasi Sejak Dini Di SMA Negeri 1 Mojolaban - Prima Putra, Ardian; Arum Pramesti, Selviana; Qoryatunnisa, Yusrina; Permatasari, Vivi (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
Human consumption relies on basic needs, but Indonesian society's behavior is now more consumption-oriented which can lead to shopping addiction which of course has a bad impact on children. Millennials are expected to have financial literacy knowledge apart from what they learn at school. Service is carried out with an educational approach by carrying out several series of ongoing activities. The service was carried out at SMA Negeri 1 Mojolaban, Sukoharjo District, which was attended by 31 participants. This activity conveys that today's teenagers not only have to go to school but also know the importance of financial intelligence to build a consumption-free generation and avoid financial problems. The results of this activity are expected to arouse the interest of the younger generation, especially students, to learn about investment and even be able to apply it in life for the future. This activity is expected to give the impression to the participants (students) that they choose and invest at a young age, and will spend your money wisely and proactively so as not to fall into a fraudulent investment situation.